TRADISI GHATIB BEGHANYUT (RATIB BERHANYUT) PADA MASYARAKAT SIAK DI KELURAHAN KAMPUNG DALAM KECAMATAN SIAK KABUPATEN SIAK - Muhammad Khairi; Swis Tantoro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
This research discussed about the Tradition of the Ghatib Beghanyut which is a rejecting Bala Ritual by means of dhikr and prayer on the Ferri Vessel and an engine Boat that drifts following the flow of the Siak river carried out by the Siak community. The author used Tallcot Parsons Social Systems Theory to analyze the phenomenon of this research. The type of approach of this research used is descriptive qualitative by determining the subject using purposive sampling. The author interviewed 5 informants that consists of the Chairperson of the Malay Customary Institution of Siak, Khodam aides, Lurah, Religious Leaders and community leaders who know about the Ghatib Beghanyut Tradition. Based on the results of this research it is found that the origins of the Ghatib Beghanyut Tradition, which a village affected by a plague and many plagues happened to them during the Siak Kingdom. In carrying out the Ghatib Beghanyut Tradition there are several stages, this tradition is carried out once a year namely in the month of safar and held in Kampung Dalam Siak District. The parties involved in the Ghatib Beghanyut Tradition are Traditional Leaders, Community Leaders, Religious Leaders, Regents, Chief Adat, Lurahs and Siak communities as well as from other regions. In the Ghatib Beghanyut Tradition there are values contained therein such as family values, togetherness values and tranquility values. The aim of doing this Ghatib Beghanyut is to drive away or reject reinforcements and also for religious tourism. To maintaining the Tradition of Ghatib Beghanyut by tell to the family, friends and the surrounding community, or can directly invite to participate in the implementation.Keywords: Tradition, Ghatib Beghanyut, Reject Bala, Siak